The Effect of Gender Diversity and Ownership Structure on Company Reputation with Corporate Social Responsibility as Mediator - Julianto Manihuruk; Augustina Kurniasih (ARKA INSTITUTE, 2023)
Company reputation is highly important to be considered by banking management as it can influence investors' perception of the company, which ultimately affects the company's value. This study aims to analyze the influence of gender diversity and ownership structure on corporate reputation, with corporate social responsibility (CSR) as a mediating variable. The research adopts a quantitative approach and falls under the category of explanatory research. The population for this study consists of all banking companies listed on the Indonesia Stock Exchange during the observation period from 2017 to 2021. The sampling method used is non-probability sampling with a purposive sampling technique. The path analysis method is used as a data analysis technique in research using the IBM SPSS program. The research finds that managerial ownership has a significant positive impact on CSR, while gender diversity and public ownership do not affect CSR. Furthermore, gender diversity and CSR are found to have a significant positive impact on corporate reputation, whereas public ownership does not impact corporate reputation. In this study, CSR plays a mediating role in the relationship between gender diversity and managerial ownership with corporate reputation. However, CSR does not mediate the influence of public ownership on corporate reputation.